3D coronary artery elastic registration based on differential invariant signatures. Issue 6 (2nd November 2022) - Wang, Mengxiao
ABSTRACT: In this paper, a point-set similarity model (PSM) is introduced, which provides a new elastic point set registration frame by using similarity invariant signature curves. According to the potential correspondences obtained by PSM, the similarity transformations between the point sets could be estimated. Experiments on synthetic data and real data of coronary artery show that our method offers certain advantages comparing with typical methods.